Biochemical parameters of oral fluid in infants with respiratory system diseases (RSD) - Lyubchenko, Olga; Severyn, Larysa (ScienceRise: Medical Science, 2019)
This article presents the data of biochemical studies conducted in the oral liquid of infants’ teeth with respiratory system diseases (RSD) with multiple caries compared to healthy children. The purpose of the article is to determine the state of biochemical parameters of the oral fluid in young children with multiple lesions of temporary teeth and RSD. Materials and methods. The survey involved 150 young children - from 0 to 3 years old. The main group was 95 children registered with the pediatrician for RSD from the first months of life and had more than 8. The control group - 55 children without general-somatic diseases, with up to 3 children who had traumatic lesions of the tooth-jaw and area needed to remove injured teeth. Biochemical analysis was carried out in the mixed oral fluid of children. The oral fluid was collected in the morning on an empty stomach into centrifuge tubes for 10 minutes. Supernatant was used for analysis. Determination of the activity of urease in the oral fluid was carried out with Nessler’s reagent. Determination of lysozyme activity was carried out using the bacteriological method. The degree of dysbiosis in the cavity of the mouth was calculated according to the Levytsky method by the ratio of the specific activity of the urease in the oral liquid to the specific activity of lysozyme. The content of total calcium in the oral liquid was determined by color reaction with ortho-creosolftaleincomplex. The level of inorganic phosphates in the oral liquid was determined by the reaction of phosphorus with molybdic acid. The results of the research show a decrease in the antimicrobial protection and mineralizing function of the oral fluid of children with caries. As a result, in the oral cavity of infants with RSD - the main group, the activity of urease and the degree of dysbiosis increased by two times in comparison with the control group, which indicates a significant degree of contamination with opportunistic pathogenic bacteria of the oral liquid of the studied children group. Conclusions. According to the obtained indicators, reduced mineralization function of the oral liquid of the main observation group was revealed. The state of the oral cavity and multiple defeat by caries of children with RSD are grounded.